2004
DOI: 10.1111/j.0886-0440.2004.04101.x
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Cardiopulmonary Bypass:. What Is the Reality?

Abstract: Despite many years of clinical and experimental research, the contribution of cardiopulmonary bypass (CPB) and cardioplegic arrest to morbidity and mortality following cardiac surgery remains unclear. This is due, in part, to lack of suitable control group against which bypass and cardioplegic arrest can be compared. The recent success of beating heart coronary artery bypass grafting has, however, for the first time, provided an opportunity to compare the same operation, in similar patient groups, with, or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 99 publications
(238 reference statements)
3
80
0
5
Order By: Relevance
“…The role of platelets in coagulation is complex, and involves adhesion, activation, aggregation and clot stabilisation. Platelet dysfunction is a recognised side effect of cardiopulmonary bypass (CPB) and plays a significant role in peri-operative blood product transfusion rates [5,6,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of platelets in coagulation is complex, and involves adhesion, activation, aggregation and clot stabilisation. Platelet dysfunction is a recognised side effect of cardiopulmonary bypass (CPB) and plays a significant role in peri-operative blood product transfusion rates [5,6,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…The role of platelets in coagulation is complex, and involves adhesion, activation, aggregation and clot stabilisation. Platelet dysfunction is a recognised side effect of cardiopulmonary bypass (CPB) and plays a significant role in peri-operative blood product transfusion rates [5,6,[8][9][10][11].Standard thromboelastography (TEG Ò ; Haemonetics, Braintree, MA, USA) is a point of care test that measures the rate and strength of clot formation induced by thrombin, which is used as the main platelet activator [12]. Using TEG in a point of care-guided algorithm for management of post-CPB bleeding has been shown to decrease transfusion rates in complex cardiac surgery [4].…”
mentioning
confidence: 99%
“…Cardiac surgery with cardiopulmonary bypass (CPB) provokes a systemic inflammatory response that can often lead to dysfunction of major organs [1][2][3][4]. Activation of the contact system, endotoxaemia, surgical trauma and ischaemia-reperfusion injury are all potential triggers of inflammation [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, we claim that there shouldn't be any difference also in between CBP periods and between ACC periods in order to have a reliable comparison in terms of systemic inflamatory response; because many studies revealed that systemic inflammatory response is increased by longer periods of CPB and ACC. [3][4][5] In this point, we suggest that the study would be more valuable if the authors share these data with us. …”
mentioning
confidence: 93%
“…1) As the authors stated, strong systemic inflammatory response takes place due to mediators caused by contact of blood and extracorporeal surface during CBP, myocardial ischemia reperfusion secondary to aortic cross-clamping (ACC), endotoxemia and operative trauma. [2][3][4] It is obviously seen that CBP is the most important factor among these. Related to that, when the study of Geyik et al is considered, there is a general standardization of perioperative data between two groups that are distinguished up to operation period.…”
mentioning
confidence: 99%